[Olympic Games - Sydney, 2000 - Australian Internet sites - record 1] - O'Connor, Mark, 1945-; O'Neill, Susie, 1973-; Sutton, Dominique; Thorpe, Ian, 1982-; Australia. Bureau of Meteorology; Australia. Department of Immigration and Multicultural Affairs; Australia. Environment Australia; Bankstown (N.S.W.). Council; New South Wales. Department of Sport and Recreation; New South Wales. Department of State and Regional Development; New South Wales. Motor Accidents Authority; Northern Territory. Department of Education. Open Learning Support Unit.; et al. ([Canberra] : c1999-, 1999)
A collection of internet sites concerned with different aspects of Sydney 2000 Olympic Games. Includes information on olympic studies, olympic business opportunities, olympic souvenirs, travel and accommodation, local and state governments' involvements etc. New sites will be added from time to time and responsible organisations will be given an added entry.
System requirements: Some plug-ins may be required to access sound and video clips.
Title from title screen (viewed on Oct. 8, 1999).
Text, graphics, video and sound.
Mode of access: Internet via World Wide Web. Available at: http://nla.gov.au/nla.arc-c4006
Selected for archiving
Keywords: New South Wales. -- Olympic Roads and Transport Authority; Stadium Australia (Homebush Bay, N.S.W.); Sydney SuperDome; Olympics -- Bibliography